Current Landscape of Molecular Targeting Therapy in Her2 Positive Breast Cancer Cell Lines Using Monoclonal Antibodies - Balan, Aswathy; Gopal, Saravanan (Asian Journal of Biological and Life Sciences, 2024)
Different target approaches such as nanocarriers and molecular targeting are used in the treatment of HER2 positive breast cancer. The present review summarizes the most significant updated research on the monoclonal antibodies used for the treatment of HER2 positive cell lines. Now a day’s combination therapies are used by drugs with nanocarriers which enhance its high therapeutic outcome by targeting features. Incorporation of the monoclonal antibodies along with the drugs will reduce the concentration of active moiety and morbidity rate. This review concludes monoclonal antibodies suggested for HER2 positive breast cancer cell lines. Among the different monoclonal antibodies Trastuzumab, Pertuzumab, Bevacizumab, Pembrolizumab shows more targets on HER2 cell lines. From the kinase inhibitors Imatinib, Lapatinib, Nevatinib are the best one, where Erlotinib, Crizotinib, Vemurafenib shows poor candidates for the HER2 targeting cancer cell line.
Keywords: HER2; Monoclonal antibody; Nanocarriers